2015
DOI: 10.1373/clinchem.2014.228965
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolic Profiling Identifies Altered Serum Metabolites of Type 2 Diabetes Mellitus in a Prospective, Nested Case Control Study

Abstract: BACKGROUND: Application of metabolite profiling could expand the etiological knowledge of type 2 diabetes mellitus (T2D). However, few prospective studies apply broad untargeted metabolite profiling to reveal the comprehensive metabolic alterations preceding the onset of T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 45 publications
(47 reference statements)
7
80
0
Order By: Relevance
“…Similar results have also been demonstrated in other studies in both Western and Asian populations [3-5, 11, 12]. Other studies have noted that alterations in NEFA and long-chain fatty acids [2,3,5,8,9,14], carbohydrate derivatives [2,13] and tricarboxylic acid (TCA) cycle intermediate metabolites [9,10] may also be associated with an increased risk of diabetes. These observations provide novel insights into the underlying pathophysiology of diabetes and highlight the possibility that alterations in metabolites may help to identify at-risk individuals prior to the onset of diabetes, in addition to standard clinical biomarkers.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results have also been demonstrated in other studies in both Western and Asian populations [3-5, 11, 12]. Other studies have noted that alterations in NEFA and long-chain fatty acids [2,3,5,8,9,14], carbohydrate derivatives [2,13] and tricarboxylic acid (TCA) cycle intermediate metabolites [9,10] may also be associated with an increased risk of diabetes. These observations provide novel insights into the underlying pathophysiology of diabetes and highlight the possibility that alterations in metabolites may help to identify at-risk individuals prior to the onset of diabetes, in addition to standard clinical biomarkers.…”
Section: Introductionsupporting
confidence: 87%
“…Recent metabolomics studies have suggested that certain metabolites and metabolite classes may be associated with the risk of obesity, insulin resistance and type 2 diabetes [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The Framingham Offspring Study, a 12-year prospective cohort study, has shown that increases in certain branched-chain amino acids (BCAAs) (such as leucine, isoleucine and valine) and aromatic amino acids (AAAs) (such as tyrosine and phenylalanine) could predict the incidence of type 2 diabetes [6].…”
Section: Introductionmentioning
confidence: 99%
“…In an article in the current issue of Clinical Chemistry, Drogan et al (7 ) applied an untargeted metabolomic approach with a coverage of ÏŸ4500 metabolite features by ultraperformance LC-MS with a protocol specifically designed for large-scale metabolomic studies regarding robustness and repeatability. The study was nested in the wellcharacterized European Prospective Investigation into Cancer and Nutrition (EPIC)-Potsdam cohort, which has collected blood samples, detailed measurements of anthropometric parameters and blood pressure, dietary and lifestyle questionnaires, and verified clinical outcomes during a follow-up period of approximately 20 years.…”
mentioning
confidence: 99%
“…Metabolic profiles have been shown to be altered as early as 3-12 years before the diagnosis of T2DM [15][16][17]. Metabolites associated with T2DM include carbohydrates, lipids like lyso-phosphatidylcholines [17,18], fatty acids [19], acylcarnitines [20], and amino acids, particularly branched-chain amino acids (BCAAs, leucine, isoleucine, and valine) and aromatic amino acids (phenylalanine and tyrosine) [16]. Leucine, isoleucine, and valine are first converted to branched-chain keto acids (BCKAs) 4-methyl-2-oxopentanoate, 3-methyl-2-oxovalerate, and 3-methyl-2-oxobutyrate, respectively, and eventually lead to the production of C3 and C5 acylcarnitines.…”
Section: Introductionmentioning
confidence: 99%